MOLECULAR AND GENETIC INSIGHTS OF ROOT-KNOT NEMATODES PATHOGENICITY: A REVIEW - Prabina Bhandari; Anjali Thapa; Anusha Ghimire; Sunil Ojha; Srijana Saud; Sanju Aryal (Acta Scientifica Malaysia)
Plant parasitic nematode must develop molecular strategies to get around the plants defense mechanism in order to successfully enter and infect their host plants. Root cells in galls show altered gene expression, indicating morphological and physiological changes. Protein analysis and molecular databases help identify down-regulated and up-regulated genes. Microarray technology can provide large-scale gene expression data on plant-nematode interaction, aiding in understanding nematode selection and feeding site alteration, thereby identifying genes controlling cell differentiation and division. The first level of resistance is known as pre-infectional resistance, and it occurs before the nematode has entered the plant. Plants have evolved a second level of basic resistance, known as non-host immunity, against pathogens that can overcome the first level of resistance. The non-host immune system resembles the innate immune system of animals in many ways. For the enhancement of plant resistance against root knot nematode there is development of the latest plant nematode interactions and manifold approach outline in the review. We will emphasize on molecular mechanism, the way of pathogenicity the different proteins hormones needed, the resistance of host plant and the future perspective. Much research is being done on molecular mechanisms underlying interactions between plants and nematodes as well how plants react to various invasive diseases.